Biology in practice - Carrie, Johanna; etc.; Dorward, James; Robertson, John.; Russell, Livingston ([S.l.] : Oxford University Press, 1990)
A problem-solving and data-handling book written for Scottish Standard Grade. Important concepts are set in a real world context and the problems develop and reinforce understanding.